Help from the sky: Can vultures contribute to Cystic Echinococcosis control in endemic areas? - Fiammetta Berlinguer (Public Library of Science (PLoS), 2021)
Cystic echinococcosis (CE) is endemic in Sardinia and constitutes a serious public health concern due to high prevalence in livestock and humans. Despite sustained efforts, control of the disease had been unsuccessful in the region. Problematic carcass disposal due to soaring incineration costs and free access of dogs to infected carrion are dominant factors, fueling endemicity among other. As sole obligate scavenger, griffon vultures (Gyps fulvus) are uniquely specialized to eliminate carcasses swiftly and efficiently, saving on unnecessary environmental and economic costs for carrion disposal. However, following drastic population declines across Europe, griffon vultures practically went extinct in Italy. A conservation expansion program in Sardinia successfully reinforced the last remaining Italian vulture population by mitigating the main threats to its survival; food shortage. Through the establishment of supplementary feeding stations, permanent supply of livestock cadavers was provided. In this research, the management and conservation implications on the controlled disposal of carcass disposal through vulture feeding stations on the control of CE in Sardinia were assessed. During the course of the project, vultures scavenged a total of 81,361 kg of biomass, saving €90,041 in incineration costs and € 1,054 in CO2 emission. Through extrapolation of these results, a total of 5,304 kg of suspected CE infected sheep carcasses (65.3%) was calculated to have been disposed by griffons, considerably reducing the CE risk and burden in Sardinia. A quantification of the amount of biomass that could be eliminated by griffon in a succeeding conservation project was also made. These calculations implied that 162,722 kg of biomass, including 10,608 kg of infected biomass from sheep, would be consumed over a period of 5 years, further lowering the CE burden in Sardinia. Our results, driven under one health approach, emphasize the crucial and direct role of griffons in breaking the lifecycle of CE as well as their indirect role in rendering multiple ecosystem and economic services through the elimination of carcasses. Please view a video Abstract here: https://youtu.be/Tm820nPq5KE.